Instructional practices with and without empirical validity - Cook, Bryan G.; Tankersley, Melody; Landrum, Timothy J. (Bingley, U.K. : Emerald, 2016)
It is important that stakeholders are aware of practices supported as effective for students with learning and behavioural disabilities in order to provide instruction that results in improved learner outcomes. Perhaps equally important, stakeholders should also know which practices have been shown by research to be ineffective (e.g., have no, small, or inconsistent effects on learner outcomes). Special education has a long history of using practices that, though appealing in some ways, have little or no positive impact on learner outcomes. In order to bridge the gap between research and practice, educators must be aware of which practices work (and prioritize their use) and which do not (and avoid their use). In this volume, each chapter describes two practices one supported as effective by research and one shown by research to be ineffective in critical areas of education for students with learning and behavioural disabilities. Chapter authors will provide readers guidance in how to do this for each effective practices and provide concrete reasons to not do this for each ineffective practice.
Instructional practices with and without empirical validity : an introduction / Bryan G. Cook, Melody Tankersley, Timothy J. Landrum -- Two approaches for improving reading fluency : research supports repeated reading but not colored filters / Bryan G. Cook, Christina Keaulana -- Developing mathematical problem solving through strategic instruction : much more than a keyword / Paul J. Riccomini, Jiwon Hwang, Stephanie Morano -- Effective and ineffective writing practices for students with disabilities / Amy Rouse, Alyson Collins -- Picture exchange communication system and facilitated communication : contrasting an evidence-based practice with a discredited method / Jason C. Travers ... [et al.] -- Movement as behavioral moderator : what does the research say? / Amy E. Ruhaak, Bryan G. Cook -- Learning styles, learning preferences, and student choice : implications for teaching / Timothy J. Landrum, Kimberly M. Landrum -- Never say never : the appropriate and inappropriate use of praise and feedback for students with learning and behavioral disabilities / Lauren W. Collins, Lysandra Cook -- Do school-wide positive behavioral interventions and supports, not exclusionary discipline practices / Rhonda N.T. Nese, Kent McIntosh -- Deep pressure therapy doesn't reduce stereotypical behavior, function-based interventions do / Mickey Losinski, Robin Parks Ennis.
Print version record
Keywords: Education -- Special Education -- Learning Disabilities; Teaching of students with emotional & behavioural difficulties; Problem children -- Education